Infective substructures of measles virus from acutely and persistently infected cells. - Rozenblatt, S (1979)
Ribonucleoprotein from cells acutely or persistently infected with measles virus were shown to be infectious by the calcium phosphate technique. Very little or no infectivity was obtained when calcium phosphate precipitation was omitted. Electron microscopy showed that the majority of ribonucleoprotein structures isolated from acutely infected cells were folded, whereas those from persistently infected cells were linear in appearance.